Assessment of Pregnant Women’s Knowledge and Practices Toward Preterm Labor - Salwa Hazim, (Iraqi National Journal of Nursing Specialties, 2023)
Objects To assess the pregnant woman’s knowledge towards preterm labor, and identify therelationship between these women’s knowledge and practices relative to their:Socio-demographic variables.Reproductive variables, previous and present history, socialand psychological factors of pregnantwomen.Methodology: ٨ descriptive study used an assessment approach in order to assess the knowledge andpractices of pregnant women with preterm labor.A purposive sample of (100 ) pregnant women with preterm labor were selected from Al-Alwiamaternity teaching hospital , Al-Yarmook teaching hospital , Baghdad teaching hospital, Fatimat AlZahra maternity ع children hospital , Al-Na'aman general hospital, Al-Kadhimia Teaching Hospitaland Ibn-Al-Baladi maternity & children hospitals in Baghdad City. The questionnaire consisted of pan(1) which included socio-demographic characteristics previous and present obstetrical history, socialand psychological factors, and source of information and part (2) pregnant women knowledge andpractices regarding the preterm labor.Reliability and validity of the questionnaire were determined. Data were collected through the use ofthe questionnaire, the application of the interview technique and review of the pregnant womenrecords. Data were analyzed through descriptive and inferential data approach.Results: The finding of the study shows high mean of scores in women's knowledge regarding thedefinition of preterm labor, in sign and symptoms in abdominal pain only, and in warning signsregarding pain like menstrual cramps and uterine contractions, while all remaining items orientedtowards low mean of scores. Regarding practices, the results presented high mean of scores in all itemsregarding pregnant woman’s practices towards preterm labor except in attending the primary healthcare center (PHCC) and visiting specialist clinic in bleeding , nausea , vomiting and leaking liquor .٠Healthy Directorate of Baghdad/ Karkh/ Al-١'amtook Secondary Midwifery/ ministry of Health٠٠ Maternity Nursing Department /College of Nursing / University of BaghdadKnowledge and Practices Toward Preterm LaborThe finding of the study also presented a significant association between preterm labor and women'soccupation, abortion occurrence, still birth and social factors in items of overload housework, familyconflicts, and presence of sad and happy events, psychological fears, including the fear of not havingpartner support, fear of daily housework, fear of weak ability to cover their personal needs and sourceof information.The pregnant women’s practices regarding the preterm labor had a significant association withwomen’s socioeconomic status, abortion occurrence, delivery of abnormal fetus, and order ofpregnancy. Also there is an association between the practices and the social factors concerning absenceof partner support. Regarding the psychological fears there was a significant association presented inthe expecting of troubles during pregnancy.Recommendation: The study recommended that health education program can be designed andconstructed for pregnant women toward preterm labor to promote their knowledge and practices toassume an optimal level of self-management within the parameters of their problem.